PELATIHAN BAHASA INGGRIS BAGI GURU TAMAN PENDIDIKAN AL-QUR’AN DAN CARA PENGAJARANNYA - Siswoyo, Siswoyo; Novita Eka Tristiana (Universitas PGRI Adi Buana Surabaya, 2022)
English is significant for the international community. Most of the Al-Qur'an Education school teachers have not fully mastered English and how to teach it. As part of the nation's generation, teachers and students of the Qur'an Education School must be taught English as an international language. This training aims to teach English to the teachers of Al-Qur’an School and how to teach it to students. This training method uses lectures and practice. The results of English language training and how it is taught are very positive. They are taught how to teach vocabulary and speaking/ conversation. They are very interested and motivated to learn and teach it to the students.